Global impact of a Shift in foreign reserves to Euros - Breuss, Fritz; Roeger, Werner; Veld, Jan in't 1962-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructure and Logistics in Brussels, 2008)
This paper considers the potential impact of a shift in official foreign reserves from dollars to euros using a global DSGE model. This paper uses QUEST III, a multi-region global DSGE model, to study the macroeconomic effects of a gradual equalization of official foreign reserves between dollars and euros. We simulate a scenario of a shift in the composition of foreign reserves holdings from the present ratio of 65 percent dollars and 25 percent euros to equal 45 percent shares over a 10 years period. We assume imperfect substitutability between financial assets to allow this shift to have real effects. Our simulations point towards small real effects due to the reduction in real interest rates resulting from this shift in official holdings.
Economic Papers.